All-cause mortality and cardiac resynchronization therapy with or without defibrillation in primary prevention. (25th November 2020) - Bisson, A
Abstract: Aims: Cardiac resynchronization therapy with (CRTD) or without (CRTP) defibrillator is recommended in selected patient with systolic chronic heart failure and wide QRS. There is no guideline firmly indicating choice between CRTP and CRTD in primary prevention, particularly in older patients. Methods: Based on the French administrative hospital-discharge database, information was collected from 2010 to 2017 for all patients implanted with CRTP or CRTD in primary prevention. Outcomes analyses were undertaken in the total study population and in propensity-matched samples. Results: A total of 45, 697 patients were analyzed (19, 266 with CRTP and 26, 431 with CRTD). The nationwide numbers of implantations increased between 2010 and 2017 (+29.6% for CRTD, +28.8% for CRTP). Proportion of CRTP implantation over CRTD remained similar over these years. During follow up (913 days, SD 841, median 701, IQR 151–1493), incidence rate (%patient/year) of all-cause mortality was higher in CRTP (11.6%) than in CRTD patients (6.8%) (Hazard Ratio [HR] 1.70, 95% CI 1.63–1.76, p<0.001). After propensity-matched analyses, mortality of patients over 75 years-old with non-ischemic cardiomyopathy (NICM) was not different with CRTP and CRTD (HR 0.93, 95% CI 0.80–1.09, p=0.39). CRTP patients under 75 yo with NICM had a higher mortality than CRTD patients (HR 1.22, 95% CI 1.08–1.37, p=0.01). Mortality rate was also higher with CRTP than with CRTD irrespectively of age in patients with ischemic cardiomyopathy (ICM) (<75 yo: HR 1.13, 95% CI 1.04–1.33, p<0.01; ≥75 yo: HR 1.22, 95% CI 1.08–1.37, p=0.01). Conclusion: This real-life study gives up-to-date information about unselected patients implanted with CRTP and CRTD in primary prevention, and provides additional data which may help physicians choosing between CRTP and CRTD at the time of implantation. Benefit of CRTD seemed clear for all-cause mortality in patients with ICM and in patients with NICM under 75 yo. Patients over 75 yo with NICM seemed less likely to benefit from primary prevention CRTD implantation. Funding Acknowledgement: Type of funding source: None